Staphylococcus capitis isolated from bloodstream infections: a nationwide 3-month survey in 38 neonatal intensive care units - Marie Decalonne; Sandra Dos Santos; Rémi Gimenes; Florent Goube; Géraldine Abadie; Saïd Aberrane; Vanina Ambrogi; Raoul Baron; Patrick Barthelemy; Isabelle Bauvin; Olivier Belmonte; Emilie Benabid; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
To increase the knowledge about S. capitis in the neonatal setting, we conducted a nationwide 3-month survey in 38 neonatal intensive care units (NICUs) covering 56.6% of French NICU beds. We demonstrated 14.2% of S. capitis BSI ( S.cap BSI) among nosocomial BSIs. S.cap BSI incidence rate was 0.59 per 1000 patient-days. A total of 55.0% of the S.cap BSIs were late onset catheter-related BSIs. The S. capitis strains infected preterm babies (median gestational age 26 weeks, median birth weight 855 g). They were resistant to methicillin and aminoglycosides and belonged to the NRCS-A clone. Evolution was favorable in all but one case, following vancomycin treatment.

An extensive study of the genetic diversity within seven French wine grape variety collections - Frédérique Pelsy; Stéphanie Hocquigny; Ximena Moncada; Gérard Barbeau; Dominique Forget; Patricio Hinrichsen; Didier Merdinoglu (Theoretical and Applied Genetics, 2010)